KH. Asjhari Mu'thi antara al-Qur'an dan Industrialisasi di Tuban - Muhammad Saifullah (IIQ An Nur Yogyakarta, 2023)
This article reviews the biography of KH. Asjhari Mu'thi is a prominent religious teacher and figure in Tuban Regency, East Java. KH. Asjhari has an interesting experience with the Quran and its relevance to his community in Tuban, which is currently undergoing industrialization. Influenced by his firm and strict teaching style of the Quran, alongside his Islamic preaching negotiations with the materialistic tendencies of the Kerek-Tuban community, he has developed a unique personal disposition. This article will explore how this uniqueness emerged and its impact on the learning methods practised by KH. Asjhari.